Family, religion, homeland - the traditional values of poles in the process of transformation = Rodzina, religia, ojczyzna - tradycyjne wartości polaków w procesie transformacji - Boguszewski, Rafał; Bożewicz, Marta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Based on the results of national research, o?cial data and selected concepts of value transformations, the article presents a review of trends regarding recognized and realized values considered as traditionally Polish, such as the family, religion and homeland. Although they are subject to changes, the direction of these changes is not always clear and straightforward. The results of the review prove that there is a lot of ambiguity when it comes to declarations and behaviors concerning family life, Polish religiousness is drifting between secularization and desecularization, and declarative patriotism often does not manifest itself in practice and is sometimes identi?ed with nationalism.
Keywords: family; religion; homeland; secularization; traditionalism; postmodernism; rodzina; religia; ojczyzna; sekularyzacja; tradycjonalizm; postmodernizm